Optimizing the Performance of the Kamsel Unit Through Lantas Dikmas in the Framework of Reducing Traffic Accidents in the Jurisdiction of Pemalang Polres - Ricky Richardo Indo Ratu (Advances in Police Science Research Journal, 2024)
This research is motivated by the fact that the level of traffic accidents in Indonesia, especially in the jurisdiction of the Pemalang Police, is still relatively high, this is because people do not understand traffic rules. The efforts made by the Pamulang Polres are optimizing the performance of the South and South Sumatra unit through Dikmas activities. "Dikmas Lantas is a form of information activity to the community which is expected to directly affect all levels of society, both organized and non-organized" so that the rate of traffic accidents can be reduced. The purpose of this study is to analyze the performance of the Kamsel unit in reducing traffic accidents and optimizing the performance of the Kamsel unit through Dikmas Lalu in order to reduce traffic accidents in the jurisdiction of the Pemalang Police. The theories used to solve the problem are performance theory, management theory, communication theory and SWOT analysis theory The research approach used was a qualitative approach with an analytical descriptive type of research, the research focused on DikmasThen activities in reducing the number of accidents in the jurisdiction of the Pemalang Police as well as being a research location. Primary data sources were obtained directly and secondary data sources were obtained through documents and annual traffic police reports using data collection techniques in the form of interviews, observations and document studies. Based on the results of the research, the Kamsel Unit has carried out direct Dikmas well and in accordance with management theory however, it is necessary to expand the range of Dikmas and the application of South Kamsel unit communication through Dikmas Lantas is still not optimal because there are several obstacles that cause the communication pattern to be not effective and efficient.